Validation of the peak frequency of bipolar electrograms for detection of residual conduction in atrial scar tissue. (19th May 2022) - Merino, JL; Kim, S; Relan, J; Sanroman, M; Castrejon, S; Cervantes, C; De La Vieja Alarcon, JJ; Martinez Cossiani, M; Rivero Santana, B; Carton, A; Tauber Molina, P
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Abbott Background: Activation and voltage (Bi-V) maps (Panel A) based on conventional bipolar electrograms (EGMs) are influenced by both near-field (NF) and far-field (FF) EGM components. This represents a limitation in the accurate detection of residual conduction within regions of scar. Peak frequency (PF) EGM analysis may better distinguish NF from FF activation vs conventional detection methods. (Panels B & C) Purpose: 1. To validate the use of PF to detect residual conduction in a well-defined model of narrow isthmus of conduction such as subacute pulmonary vein (PV) reconnection following atrial fibrillation ablation. 2. To compare discrimination value of PF and conventional Bi-V to detect such isthmuses. Methods: Bi-V and activation maps were acquired during redo PV isolation (PVI) procedures using a rectangular 16-pole catheter (HD-Grid). LA-PV conduction was assessed during coronary sinus (CS) pacing (500ms cycle length). Any conduction gap (GAP) site at which PVI was established using ≤3 focal radiofrequency applications was analyzed. (Panel A) EGMʼs ≤1cm from the site of PVI were classified as GAP (vs EGMʼs ≥1cm - No-Gap). (Panel B) Results: 28 GAPs were found in 12 of 14 consecutive patients in the study. 3, 976 EGMʼs (1, 547 GAP vs 2, 429 No-GAP) were analyzed. GAP regions showed significantly higher PF than No-GAP regions (345 ±135 vs 181±116 Hz, P<0.0001) (Panel E). GAP regions also showed significantly higher BiV than No-GAP regions (1.86±2.11 mV vs 0.62±1.22 mV, P<0.0001) (Panel D). ROC curves for GAP vs No-GAP discrimination were better for PF (AUC 0.84) than for Bi-V (AUC 0.74) with optimal cutoffs of 240 Hz and 0.2 mV, respectively. (Panel F) Conclusion: PF better detects residual conduction within an atrial scar region than conventional Bi-V. The PF cutoff value for gap discrimination in the PV antra is 240 Hz.